Development of adenovirus capsid proteins for targeted therapeutic delivery - Medina-Kauwe, Lali K (2013)
The outer shell of the adenovirus capsid comprises three major types of protein (hexon, penton base and fiber) that perform the majority of functions facilitating the early stages of adenovirus infection. These stages include initial cell-surface binding followed by receptor-mediated endocytosis, endosomal penetration and cytosolic entry, and intracellular trafficking toward the nucleus. Numerous studies have shown that the penton base contributes to several of these steps and have supported the development of this protein into a delivery agent for therapeutic molecules. Studies revealing that the fiber and hexon bear unexpected properties of cell entry and/or nuclear homing have supported the development of these capsid proteins, as well into potential delivery vehicles. This review summarizes the findings to date of the protein–cell activities of these capsid proteins in the absence of the whole virus and their potential for therapeutic application with regard to the delivery of foreign molecules.